2022
DOI: 10.1111/jsr.13613
|View full text |Cite
|
Sign up to set email alerts
|

Dream‐enactment behaviours during the COVID‐19 pandemic: an international COVID‐19 sleep study

Abstract: Summary There has been increasing concern about the long‐term impact of coronavirus disease 2019 (COVID‐19) as evidenced by anecdotal case reports of acute‐onset parkinsonism and the polysomnographic feature of increased rapid eye movement sleep electromyographic activity. This study aimed to determine the prevalence and correlates of dream‐enactment behaviours, a hallmark of rapid eye movement sleep behaviour disorder, which is a prodrome of α‐synucleinopathy. This online survey was conducted betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…EDS is highly prevalent in synucleionopathies suggesting that similar neural networks regulate sleepiness, dream-enacting, and olfactory function. On the other hand, in our previous study we found an association between COVID-19 infection and dream enactment behavior that may suggest the involvement of mental factors rather than central effects of COVID-19 infection [ 32 ].…”
Section: Discussionmentioning
confidence: 93%
“…EDS is highly prevalent in synucleionopathies suggesting that similar neural networks regulate sleepiness, dream-enacting, and olfactory function. On the other hand, in our previous study we found an association between COVID-19 infection and dream enactment behavior that may suggest the involvement of mental factors rather than central effects of COVID-19 infection [ 32 ].…”
Section: Discussionmentioning
confidence: 93%
“…A polysomnographic study comparing patients with PTSD to those with idiopathic RSBD and healthy controls found a higher rate of REM sleep with atonia, as measured by electromyography, in those with PTSD [55]. A larger study based on self-report data, including over 20,000 adults in the context of the COVID-19 pandemic, found a significant positive association between self-reported PTSD symptoms and dream enactment behavior, which is a symptom of RSBD [56]. Key: ++, positive evidence from more than one study; +, positive evidence from a single study; ±, conflicting results; ?, positive results only in sub-group analyses, or results of uncertain significance.…”
Section: Sleep-related Studiesmentioning
confidence: 99%
“…Restricted mobility and irregularity of the sleep-wake cycle hours, along with overall psychological distress and worry about the future, have affected the amount and quality of sleep in the general population. Physical exercise is well supported by the literature as a nonpharmacological treatment method for sleep disorders; however, COVID-19 patients, either bedridden or simply quarantined, lack the required exercise to maintain healthy sleep [82], and even incidents of dream-enactment behaviors and other parasomnias have been reported and have been attributed to physical restriction during quarantine that may potentially alter their physical activity pattern [83]. Furthermore, they are at risk of developing circadian rhythm problems due to changes in daytime routine, possible daytime naps, and insufficient exposure to natural light [82].…”
Section: Quarantine-inflicted Sleep Pathologiesmentioning
confidence: 99%